2017
DOI: 10.3233/jnd-170280
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Duchenne Muscular Dystrophy: A Study of 5345 Patients from the TREAT-NMD DMD Global Database

Abstract: Background:Recent short-term clinical trials in patients with Duchenne Muscular Dystrophy (DMD) have indicated greater disease variability in terms of progression than expected. In addition, as average life-expectancy increases, reliable data is required on clinical progression in the older DMD population.Objective:To determine the effects of corticosteroids on major clinical outcomes of DMD in a large multinational cohort of genetically confirmed DMD patients.Methods:In this cross-sectional study we analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 39 publications
7
136
2
4
Order By: Relevance
“…There are well-documented benefits of longterm corticosteroid use in DMD on improving functional milestones, delaying development of scoliosis and cardiomyopathy, delaying the need for respiratory support, and improving survival and quality of life, [23][24][25][26] and there is a growing consensus recommending continued use of corticosteroids after loss of ambulation. 2,4 Recently, increased evidence has shown that the type of steroid 27 (prednisone or deflazacort) and the specific regimen 28 (daily vs. intermittent), as well as age at initiation 29,30 and duration of treatment, 31 all have a differential impact on individual clinical milestones.…”
Section: Non-invasive and Invasive Ventilation And Coughmentioning
confidence: 99%
“…There are well-documented benefits of longterm corticosteroid use in DMD on improving functional milestones, delaying development of scoliosis and cardiomyopathy, delaying the need for respiratory support, and improving survival and quality of life, [23][24][25][26] and there is a growing consensus recommending continued use of corticosteroids after loss of ambulation. 2,4 Recently, increased evidence has shown that the type of steroid 27 (prednisone or deflazacort) and the specific regimen 28 (daily vs. intermittent), as well as age at initiation 29,30 and duration of treatment, 31 all have a differential impact on individual clinical milestones.…”
Section: Non-invasive and Invasive Ventilation And Coughmentioning
confidence: 99%
“…In this recessive X-linked monogenic disorder, mutations in the DMD gene lead to the loss of a functional dystrophin protein, resulting in a progressive - yet severe - muscle wasting phenotype (1). In patients, symptoms usually appear in early childhood (2-5 years old) and worsen with age, imposing the use of wheelchair before 15 and leading to premature death by cardiac and/or respiratory failure(s) mostly around 30 years of age (2).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, natural history studies are facilitating a definition of predictive clinical end points and biomarker development. Studies of hundreds of patients in international collaborative studies aim to identify early sensitive and reliable outcome measures that are predictive of later quality of life changes — these are then strong PD end points …”
Section: Extrapolation Of Clinical Outcomes As Pd End Pointsmentioning
confidence: 99%
“…Studies of hundreds of patients in international collaborative studies aim to identify early sensitive and reliable outcome measures that are predictive of later quality of life changesthese are then strong PD end points. 29,30 In eosinophilic esophagitis, the pathophysiology of the disease is similar in adults and children, and one of the main treatment goals of eosinophilic esophagitis is to reduce symptoms. 31 However, variable symptomatology across pediatric and adult populations complicates the development of instruments to measure both patient-and observer-reported outcomes.…”
Section: Extrapolation Of Clinical Outcomes As Pd End Pointsmentioning
confidence: 99%